Case Report: Successful Treatment of Five Critically Ill Coronavirus Disease 2019 Patients Using Combination Therapy With Etoposide and Corticosteroids - Aoyagi, Tetsuji; Sato, Yukio; Baba, Hiroaki; Shiga, Takuya; Seike, Issei; Niitsuma Sugaya, Ikumi; Takei, Kentarou; Iwasaki, Yudai; Oshima, Kengo; Kanamori, Hajime; Yoshida, Makiko; Saito, Koji; et al. (Frontiers in Medicine, 2021)
Acute respiratory distress syndrome (ARDS) is the leading cause of mortality in hospitalized patients with coronavirus disease 2019 (COVID-19) because of limited effective therapies. During infection, the accumulation and activation of macrophages and monocytes in the lungs induce inflammatory mediators and contribute to tissue injury, leading to ARDS. However, therapeutic strategies that directly target activated macrophage and monocytes have not been reported. Combination treatment with etoposide (a cytotoxic agent) and a corticosteroid has been widely used for treating hemophagocytic lymphohistiocytosis characterized by the systemic activation of macrophages with overwhelming inflammation. Herein, we present five cases of COVID-19-associated ARDS treated with etoposide and corticosteroids. Three of the five patients were over 65 years of age and had various underlying diseases, including multiple myeloma. Four patients required invasive mechanical ventilation (MV), and one patient refused to be placed on MV due to underlying diseases. All patients were pre-treated with antiviral and/or other anti-inflammatory agents, but their condition deteriorated and hyperinflammation was noted. All five patients responded well to treatment and had an immediate response, as reflected by improvement in their respiratory condition and inflammatory marker levels and rapid resolution of fever after etoposide administration; however, some patients required a second dose of etoposide and longer course of steroids. All patients recovered, and there were no severe adverse events related to the drugs. Following successful treatment in these five patients, we plan to conduct a clinical trial to evaluate the efficacy and safety of combination therapy with etoposide and corticosteroid for treating COVID-19 patients in Japan.